2012
DOI: 10.1002/pbc.24303
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of Group D eyes in bilateral retinoblastoma patients treated with chemoreduction and low‐dose IMRT salvage

Abstract: Kaplan-Meier estimates of eye survival of Group D eyes in bilateral patients at 12 months is 82% (95% confidence interval [CI] 70.1-89.7%); at 60 months eye survival is estimated to be 68% (95% confidence interval [CI] 55.4-82.8%). Systemic treatment for retinoblastoma demonstrated a high rate of globe preservation with acceptable complications and many eyes retaining functional vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 40 publications
3
94
1
Order By: Relevance
“…Globe salvaging treatment for Group E retinoblastoma is done only if the patient has bilateral disease wherein the contralateral eye will also require systemic therapy for salvage. The treatment paradigms at our center have been described previously [9,10,11]. …”
Section: Methodsmentioning
confidence: 99%
“…Globe salvaging treatment for Group E retinoblastoma is done only if the patient has bilateral disease wherein the contralateral eye will also require systemic therapy for salvage. The treatment paradigms at our center have been described previously [9,10,11]. …”
Section: Methodsmentioning
confidence: 99%
“…With our protocol we maintained a 93% (68/73) salvage rate for eyes with Group A-C disease, a 55% (6/11) salvage rate for treated eyes with Group D disease, and a 25% (4/16) salvage rate for eyes with Group E disease. All of these success rates are comparable to standard dose CRD in older age groups [17,18], suggesting that concerns regarding tumor drug resistance with lower dose chemotherapy regimens may be unfounded in this younger group of patients. …”
Section: Discussionmentioning
confidence: 55%
“…One patient developed severe hearing loss that required hearing aids. Another patient developed non-etoposide-associated AML 12 months after the completion of CRD, and this case has been described previously [17]. All patients were alive and no other secondary malignancies have been identified at a median follow-up of 52.9 months (range 1-148).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…It was reported that the cure rate reached up to 75% after 6 courses of chemotherapy (carboplatin, etoposide, vincristine and cyclophosphamide as )combined with laser, thermotherapy and other topical therapies (Künkele et al, 2013). The research of Berry et al showed that the cure rate of binoculus RB treated by chemoreduction was 47%, with the survival time of 82% of the patients was more than 12 months and 68% more than 60 months (Berry et al, 2013). The application of chemoreduction significantly increase the retention rate of RB patients, but new RB still occur in 24% of patients during or after the treatment, most of which are in infancy or have a family history of the disease (Shields et al, 2003).…”
Section: Discussionmentioning
confidence: 99%